Devising an automated method to form the content of educational specialization disciplines of maximum utility for implementation in the professional field - Astapenko, Natalya; Koshekov, Kayrat; Ponomarev, Grigoriy; Seidakhmetov, Beken; Fedorov, Igor; Zuev, Dmitriy (Eastern-European Journal of Enterprise Technologies, 2021)
The rapid growth and emergence of breakthrough technologies in the information and communication field requires annual adjustment and modernization of curricula for specialization disciplines in accordance with the current market requirements. A method of prompt response of the educational environment to the requirements of the external environment, based on the creation of a pool of demanded learning outcomes, is proposed. The object of the research is the process of formation of the required content of specialization disciplines. A formalized method for forming the content of educational disciplines of specialization of maximum utility for implementation in the professional field is described based on expert assessments of representatives of the job market. An algorithm for finding a set of learning outcomes for the identified conditions was devised. A software tool that includes a database and two components: a web interface for collecting and primary processing of information and a C++ program module for automating the main algorithm was developed. The result of the software tool is a pool of learning outcomes recommended for implementation in the content of the educational program. The results of an experimental study based on test data, which proved the accuracy of the calculations of the software component, were presented. Verification of data in the area of web technologies and web programming made it possible to identify a list of learning outcomes for implementation in the educational program «Information Systems». The algorithm developed as a result of research can be used to form the demanded content of elements of educational programs in any industry. It is supposed to develop the proposed method when creating interactive training programs on the technological processes of aircraft repair at the enterprises of the aviation industry.